Double grain boundary configurations on graphite surfaces. (December 2020) - Capasso, A.; Muñoz-Rojas, F.; Gupta, B.; Motta, N.; Placidi, E.
Abstract: We investigated the atomic structure of different kinds of grain boundaries on highly oriented pyrolytic graphite (HOPG) by scanning tunneling microscopy. We categorized several grain boundary configurations as a function of the misorientation angle between the adjacent grains, highlighting the occurrence of double grain boundaries ( i.e., systems of two grain boundaries separated by a nanometric-scale inner region with specific atomic arrangement) for misorientation angles in the range 22°–32°. By using Molecular Dynamics simulations, we analyzed the structure and energy stability of single and double grain boundaries according to the misorientation angle. The experimental evidence is corroborated by Molecular Dynamics results and total energy calculations, which found a comparable stability between single and double grain boundaries for the same misorientation angle range. Our combination of experimental measurements and theoretical calculation extends the understanding of the structural configuration of large angle grain boundaries beyond the range of misorientation angles reported to date. Graphical abstract: Image 1